Finding Mecca in America: How Islam is Becoming an American Religion By Mucahit Bilici (Chicago and London: University of Chicago Press, 2012. 257 pages.) (American Journal of Islam and Society, 2013)
The notion that Islam is “Becoming an American Religion” may be unnervingto those who see America’s roots in its Christian, and more recentlyJudeo-Christian, heritage. Yet, given the rate of growth and development ofAmerican Muslim institutions and social networks, it may be more apt tospeak of Islam as part of an American multireligious heritage. In FindingMecca in America: How Islam is Becoming an American Religion, MuchitBilici explores the rapid increase of American Muslim educational, cultural,religious, and civic institutions, as well as how September 11, the so-calledwar on terror, and most recently media coverage of the Arab Spring have givenAmerican Muslims a unique visibility in the American public sphere.Bilici demonstrates how multifarious individuals and coalitions havebanded together to counter negative public sentiments toward Islam and Muslims,to advocate for legal protections against discrimination, and to help fashiona cultural and religious niche for the community’s faith, practices, andpresence. Even as public narratives about Muslims tend to emphasize “elementsof chaos, instability, and danger,” sympathetic representations of AmericanMuslims as “next-door neighbors” or “decent Americans struggling fortheir civil rights and in need of empathy, understanding and respect” are becomingmore prevalent in major media venues from National Public Radioto the New York Times (p. 3). In turn, Muslims are demonstrating their collectiveabilities to define authentically American identities through social andpolitical activism, forms of strategic public outreach, even ethnic comedy ...